Effectıveness of Islamıc Educatıon on Indıan mualaf (Converts) in Selangor, Malaysıa - Dakir J.; Tibek S.R.H.; Sham F.M.; Othman M.Y.H.; Zaharın, A.; Jalıl, M.H.; Yahya S.A.; Ibrahim S.M.I.; Ismaıl, M.I. (Sakarya University, 2024)
Indexed by Scopus